2023
DOI: 10.1039/d3nr02487c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical PdNi alloy nanochains coupled with Ni(OH)2 nanosheets to enhance CO-poisoning resistance for the methanol oxidation reaction

Abstract: Hybridizing Pd-based electrocatalysts with Ni-based species has been recognized as an effective pathway to enhance the catalytic performance for methanol oxidation reaction (MOR). However, doping Ni-based species with heterogeneous valence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…These lattice phases scarcely exist alone, but they were usually mixed together disorderly to form a chaotic structure, resulting in most of the Pd–Ni nanoparticles hardly distinguishing the existence of any single lattice plane, as was denoted by the white circles in Figure f. Therefore, numerous lattice dislocations appeared in the Pd–Ni nanoparticles due to the presence of the multiple lattice phases with different lattice spacings . These lattice dislocations could cause abundant lattice defects existing in the Pd–Ni nanoparticles, owing to the NiB, Pd 2 B, and Ni nanoclusters inserted into the Pd–Ni nanoparticles .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These lattice phases scarcely exist alone, but they were usually mixed together disorderly to form a chaotic structure, resulting in most of the Pd–Ni nanoparticles hardly distinguishing the existence of any single lattice plane, as was denoted by the white circles in Figure f. Therefore, numerous lattice dislocations appeared in the Pd–Ni nanoparticles due to the presence of the multiple lattice phases with different lattice spacings . These lattice dislocations could cause abundant lattice defects existing in the Pd–Ni nanoparticles, owing to the NiB, Pd 2 B, and Ni nanoclusters inserted into the Pd–Ni nanoparticles .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, numerous lattice dislocations appeared in the Pd− Ni nanoparticles due to the presence of the multiple lattice phases with different lattice spacings. 28 These lattice dislocations could cause abundant lattice defects existing in the Pd−Ni nanoparticles, owing to the NiB, Pd 2 B, and Ni nanoclusters inserted into the Pd−Ni nanoparticles. 29 Additionally, these lattice dislocations also led to plenty of the lattice strain among the NiB, Pd 2 B, Ni, and Pd nanoclusters in the Pd−Ni nanoparticles.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…These findings suggested that Ni in NiPdH NNs primarily exists as Ni 2+ . This could be attributed to the fact that Ni metal is oxyphilic and easily oxidized when exposed to air . The XPS survey spectra of NiPdH NNs and PdNi NPs are presented in Figures S10 and S11, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the fact that Ni metal is oxyphilic and easily oxidized when exposed to air. 30 The XPS survey spectra of NiPdH NNs and PdNi NPs are presented in Figures S10 and S11, respectively. The Pd−N signal located at 397.3 eV was absent.…”
Section: Formation Mechanismmentioning
confidence: 99%
“…38–42 PtPd and NiPd alloys exhibited high stability, durability, and CO tolerance as electrodes in applications such as the ORR, electrooxidation of alcohols and formic acid, and CO 2 electroreduction. 41–47 Considering the catalytic performance and cost-effectiveness, designing NiPtPd NPs with a Ni-rich core and a shell rich in Pt and Pd will be ideal. In the field of catalysts, the above structure is unique with the following advantages: (a) reduced consumption of Pt and Pd per unit volume, (b) strong resistance under acidic and basic conditions, and (c) high catalytic properties.…”
Section: Introductionmentioning
confidence: 99%